EVALUASI KERUSAKAN JALAN DAN SOLUSI PENANGANAN DENGAN METODE PAVEMENT CONDITION INDEX PADA JALAN GEMOLONG-ANDONG - Putri, Ade Artianto; Yuono, Teguh; Sumina, Sumina; Atmaja, Ade Sandhy (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
In today's developments, very rapid population growth has resulted in increasing human activities and needs, including road infrastructure. The construction of roads as infrastructure facilitates mobility and accessibility of economic, socio-cultural, and tourism activities for the community. Gemolong-Andong Highway, Central Java is a provincial road that connects Sragen Regency with Semarang Regency. Gemolong-Andong Road is a road that is heavily used by heavy vehicles such as food trucks, sand trucks, and tourist buses, including cargo vehicles that can be used in one lane and two ways. This road is 6 m wide. The activity of heavy capacity and large-sized cars also influence road conditions, so that transportation activities on roads between districts show an unbalanced development between the condition of the road structure and the road usage capacity, which causes the road to be easily damaged. Based on the observations made, it can be identified what damage occurred on the Gemolong-Andong STA 26+600-28+600 road. The problems that occur in Jalan Gemolong-Andong require research because there is a lot of damage such as holes, edge cracks, crocodile cracks, and other damage. Vehicle loads and weather factors cause the Gemolong-Andong road to disrupt road users' activities, resulting in slower vehicle travel times. Accordingly, calculations of traffic density volume and soil-bearing capacity are carried out. Then, from all the work, the total cost required is IDR 222,633,843 (Two hundred twenty-two million six hundred thirty-three thousand eight hundred and forty-three rupiah).